Fatigue crack threshold analysis of TiAl SENT and CC specimens – Influence of starter notch and precracking. (June 2020) - Eck, S.; Maierhofer, J.; Tritremmel, C.; Gaenser, H.-P.; Marsoner, S.; Martin, N.; Pippan, R.
Abstract: Due to their low density, excellent high temperature strength and good oxidation resistance, TiAl alloys are being used for components in commercial aero-engines. Fatigue crack threshold analysis is a safety critical input to the component design. Fatigue properties of a TiAl alloy with a near fully lamellar microstructure were investigated in detail by means of fatigue crack growth testing. Two different types of standard fatigue specimens (SENT – single edge notch tension and CC – corner crack) were machined and subjected to cyclic loading at temperatures between room temperature and 700 °C with a stress ratio R = 0.1. The present work examines the influences of sample geometry, starter notch width, starter notch radius and the effect of compression precracking on the measured threshold stress intensity factor range ΔKth . The results show to which extent the different specimen geometries and starter notch preparations yield the same fatigue crack growth (FCG) threshold results and which setup yields in the most conservative results, i.e. lowest crack growth thresholds for the same material and load condition. Highlights: Fatigue crack growth testing of TiAl alloy 4522XD between 25 °C and 700 °C at R = 0.1. Graphs illustrating the evaluation of the crack growth threshold ΔKth via DCPD. Effect of starter notch preparation and pre-cracking for SENT and CC geometries on ΔKth, and. Comparability of ΔKth achieved with SENT and CC specimens between 25 °C and 700 °C.